2021
DOI: 10.25011/cim.v44i4.37592
|View full text |Cite
|
Sign up to set email alerts
|

ICD-10 Diagnostic Coding for Identifying Hospitalizations Related to a Diabetic Foot Ulcer

Abstract: Purpose: To estimate the positive predictive value (PPV) of Canadian ICD-10 diagnostic coding for the identification of hospitalization related to a diabetic foot ulcer (DFU). Methods: Hospitalizations related to a neuropathic and/or ischemic DFU were identified from the Discharge Abstract Database (DAD) records of a single Canadian tertiary care hospital between April 1, 2002 and March 31, 2019. The first coding approach required a most responsible diagnosis (MRDx) code for diabetes-specific foot ulceration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4,8 A US cohort study revealed that diabetes mellitus had association with a significantly increased risk of hospitalization for infections, and the risk was most prominent for foot infection (HR, 5.99; 95% CI, 4.38-8.19). 25 Without proper treatment, foot infections may progress from cellulitis to osteomyelitis; cellulitis may also lead to foot ulcers. A deteriorated foot infection may necessitate an amputation to save a life.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 A US cohort study revealed that diabetes mellitus had association with a significantly increased risk of hospitalization for infections, and the risk was most prominent for foot infection (HR, 5.99; 95% CI, 4.38-8.19). 25 Without proper treatment, foot infections may progress from cellulitis to osteomyelitis; cellulitis may also lead to foot ulcers. A deteriorated foot infection may necessitate an amputation to save a life.…”
Section: Discussionmentioning
confidence: 99%
“…The following Canadian Classification of Health Intervention (CCI) codes were used to identify major LEA: 1VC93, 1VG93, 1VQ93, and 1WA93. Persons also needed to have a diagnosis of peripheral vascular disease and/or diabetes prior to or at the time of initial LEA hospitalization [ 26 , 27 ]. We excluded those not eligible for health coverage in Ontario or a non-resident of Ontario, invalid death date (died before admission, or died during initial stay), those who were less than 18 years of age or older than 105 years, missing or invalid sex or date of birth, those with a previous major dysvascular LEA event (looked back to 2002), and those with amputations due to trauma, cancer, congenital, or orthopedic causes (see Fig 1 for cohort flow diagram).…”
Section: Methodsmentioning
confidence: 99%